Alpha‐thalassaemia promotes frequent vaso‐occlusive crises in children with sickle cell anaemia through haemorheological changes. Issue 8 (18th January 2017) - Renoux, Céline; Connes, Philippe; Nader, Elie; Skinner, Sarah; Faes, Camille; Petras, Marie; Bertrand, Yves; Garnier, Nathalie; Cuzzubbo, Daniela; Divialle‐Doumdo, Lydia; Kebaïli, Kamila; Renard, Cécile; et al.
Abstract: Background: Sickle cell anaemia (SCA) is a severe hereditary haemoglobinopathy characterised by haemorheological abnormalities, which play a role in the occurrence of several acute and chronic clinical complications. While β S ‐haplotypes and alpha‐thalassaemia modulate SCA clinical severity, their effects on blood rheology have been incompletely described. The aim of this study was to test the effects of these genetic modifiers on the haemorheological properties and clinical complication of children with SCA. Procedure: Steady‐state haemorheological profile, biological parameters, β S ‐haplotypes, alpha‐globin status, vaso‐occlusive crisis (VOC) and acute chest syndrome frequencies were analysed in 128 children (aged 5 to 18 years) with SCA. Results: Patients with alpha‐thalassaemia showed increased red blood cell (RBC) deformability and aggregation compared to those without. Median VOC rate was higher in patients with homozygous alpha‐thalassaemia compared to those with a normal alpha genotype. Conversely, the haemorheological profile and clinical complications were not influenced by the β S ‐haplotypes in our study. Conclusion: Our results demonstrate that alpha‐thalassaemia is associated with higher risk for VOC events in children with SCA, which may be due in part to its effects on RBC deformability and aggregation.